Speed Control of a Doubly Fed Induction Motor using Fuzzy Logic Techniques - Ben Attous, D; Bekakra, Youcef (School of Electrical Engineering and Informatics, Bandung Institute of Techonolgy, Indonesia, 2010)
This paper presents a comparison between a fuzzy logic controller and a conventional IP controller used for speed control with a direct stator flux orientation control of a doubly fed induction motor. The effectiveness of the proposed control strategy is evaluated under different operating conditions such as of reference speed and for load torque step changes at nominal parameters and in the presence of parameter variation. Simulation results show that the fuzzy logic controller is more robust than a conventional IP controller against parameter variation and uncertainty, and is less sensitive to external load torque disturbance with a fast dynamic response.
Article
Keywords: direct stator flux orientation control, doubly fed induction motor, fuzzy logic controller, Fuzzy PI controller, conventional IP controller